The Influence of implementing the new student admissions policy on the management of the student admissions program to realize the effectiveness of student admissions - Hayat, Yusep Saepul; Salamah , Ummu; Masripah, Masripah (Universitas Wiralodra, 2023)
The educational problems faced include the low effectiveness of new student admissions in madrasah education. It is thought that the management of the student admissions program could have been more optimal due to the influence of the implementation of the new student admissions policy, which has not been optimal, resulting in the effectiveness of student admissions not being optimal. The research aims to analyze the implementation of the new student admissions policy on managing the student admissions program to realize the effectiveness of student admissions. The research method used in this research is the analytical description method using observation, survey, and documentation study techniques. The data analysis technique used to answer this research hypothesis is statistics using a path analysis model. The population and respondents for this research were 51 teaching and educational staff at Madrasah Tsanawiyah Al-Mu'awanah and Madrasah Tsanawiyah Nurul Hidayatul Iman. The results of testing the central hypothesis using path analysis testing are: